Rapeseed meal in feed for Atlantic salmon 2 / Repjumjöl í fóðri fyrir lax 2 - Árnason, Jón; Sigurgeirsson, Ólafur Ingi; Kristjánsson, Gunnar; Simonsen, Morten; Smárason, Birgir Örn (Zenodo, 2022)
This report provides a summary of progress and main results of the AVS funded research & innovation project “rapeseed meal in feed for Atlantic Salmon 2”. The objective of the project was to investigate the effect of rapeseed meal inclusion in feed on growth, feed utility and fillet composition in Atlantic salmon. : Funding: AVS rannsóknarsjóður í sjávarútvegi (R 19 013-19)